Analysis of the blood flow in a microchannel with a bifurcation - Oliveira, Brigitte (2009)
In vitro experiments allow precise measurement and control over relevant physiological variables. Thus, in the present study we have used a lithography technique to fabricate a rectangular PDMS microchannel with a bifurcation. By using a confocal micro-PTV system, we have measured the effect of bifurcation on the flow behaviour of both fluorescent particles diluted in pure water and red blood cells (RBCs) in concentrated suspensions. After performing simulations with the commercial finite element software package POLYFLOW®, some experimental results were compared with the numerical results. Our preliminary results suggest that the RBC paths may suffer fluctuations on the transversal direction caused by RBCs obstruction around the neighbourhood of the diverging point of the bifurcation.